Non-static spinning fluid model in Einstein–Cartan theory of gravitation - L. N. Katkar; D. R. Phadatare (European Physical Journal C: Particles and Fields)
Abstract By harnessing the power of differential forms, especially suited for a non-Riemannian space-time of Einstein–Cartan theory, we have successfully solved the field equations for a Weyssenhoff fluid-a fascinating source of gravitation and spin. Our innovative approach is based on a simple yet elegant equation of state, with two distinct cases: (i) $$ρ $$ ρ = p, and (ii) $$ρ = 3p$$ ρ = 3 p , and an exponential relationship $$e^{μ } = e^{nν }$$ e μ = e n ν . We explore the fascinating physical and geometrical properties of these ground-breaking solutions, uncovering new insights into the mysteries of gravitation and the behavior of matter under extreme conditions.